2006
DOI: 10.1177/0037549706069341
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factorization of Plants to Compute Their Functional and Architectural Growth

Abstract: Numerical simulation of plant growth has been facing a bottleneck due to the cumbersome computation implied by the complex plant topological structure. In this article, the authors present a new mathematical model for plant growth, GreenLab, overcoming these difficulties. GreenLab is based on a powerful factorization of the plant structure. Fast simulation algorithms are derived for deterministic and stochastic trees. The computation time no longer depends on the number of organs and grows at most quadraticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 18 publications
0
65
0
Order By: Relevance
“…In this paragraph, we present the generic mathematical frame of the GreenLab model [3,28]. For applications on real plant species, different versions are derived from this common frame, to adapt to the specificities of each species.…”
Section: Time and Architecture Discretizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paragraph, we present the generic mathematical frame of the GreenLab model [3,28]. For applications on real plant species, different versions are derived from this common frame, to adapt to the specificities of each species.…”
Section: Time and Architecture Discretizationmentioning
confidence: 99%
“…In the next section, we detail only the equations necessary for our case study but a more comprehensive description can be found in [3,25].…”
Section: Time and Architecture Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The architectural development of plant is described as a sequence of growth unit appearances as well as the expansion of the organs constituting the growth units ( [4], [2]). Generally for crops, the thermal time elapsing between successive appearances of phytomers can be considered as constant and is called phyllochron ( [23]).…”
Section: Organogenesis and Demandmentioning
confidence: 99%
“…Some of them are currently able to model plant development and production, under constraints from a variable resource environment, especially in terms of light, water and temperature [6]. Nevertheless, in such approaches, the interaction between plant models and resources is limited.…”
Section: Introductionmentioning
confidence: 99%